AKUNTANSI BUMDES DI DESA JE’NEMADINGING KABUPATEN GOWA - Asbi Amin; Niken Probondani Astuti (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2021)
Je’nemadinging village is one of the villages located in Pattalassang District, Gowa Regency. Since the existence of BUMDes in this area, all these transactions are only recorded when money comes in and money goes out with a simple count. BUMDes managers have never prepared financial reports as appropriate for a business-oriented entity. This is due to the lack of knowledge of managers because none of their educational backgrounds come from the economic sector. On the basis of the problems that occur with partners, this PKM program needs to be carried out. This PKM activity was carried out at the Je'nemadinging village office. The model used in the lecture method, tutorial method and discussion. The result of this PKM is that the BUMDes Management can make bookkeeping in the form of recording incoming and outgoing money in accordance with generally accepted rules. In addition, BUMDes management has understood the accounting  for cash receipts, cash disbursements, sales and purchases to the preparation of financial reports